Potato Vine Killing or Desiccation - Chad M. Hutchinson; William M. Stall (EDIS, 2007)
Revised! HS-925, a 3-page fact sheet by Chad M. Hutchinson and William M. Stall, describes mechanical, chemical, and combination methods of killing potato vines to ensure tuber maturity at harvest. Includes a table listing potato vine desiccants and references. Published by the UF Department of Horticultural Sciences, November 2007.